2020
DOI: 10.3310/hta24510
|View full text |Cite
|
Sign up to set email alerts
|

Avatrombopag and lusutrombopag for thrombocytopenia in people with chronic liver disease needing an elective procedure: a systematic review and cost-effectiveness analysis

Abstract: Background There have been no licensed treatment options in the UK for treating thrombocytopenia in people with chronic liver disease requiring surgery. Established management largely involves platelet transfusion prior to the procedure or as rescue therapy for bleeding due to the procedure. Objectives To assess the clinical effectiveness and cost-effectiveness of two thrombopoietin receptor agonists, avatrombopag (Doptelet®;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
11
1
Order By: Relevance
“…Regarding cost of these agents, the NICE concluded that based on a recent cost analysis by the pharmaceutical company manufacturing Lusutrombopag, that it was "…highly likely that lusutrombopag would reflect a good use of scarce NHS resources" [21] . This contrasts the recent National Institute for Health Research abstract which concluded that Avatrombopag and Lusutrombopag were not cost effective given their lack of long-term benefit and increase in drug cost [30] .…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding cost of these agents, the NICE concluded that based on a recent cost analysis by the pharmaceutical company manufacturing Lusutrombopag, that it was "…highly likely that lusutrombopag would reflect a good use of scarce NHS resources" [21] . This contrasts the recent National Institute for Health Research abstract which concluded that Avatrombopag and Lusutrombopag were not cost effective given their lack of long-term benefit and increase in drug cost [30] .…”
Section: Discussioncontrasting
confidence: 73%
“…Several studies have assessed the clinical effectiveness in relation to the estimated cost-effectiveness of avatrombopag, lusutrombopag, and platelet transfusions. Some results of these analyses are equivocal or conflicting [ 91 , 92 , 93 , 94 ]. For example, Mladsi et al, reported that avatrombopag reduced the need for platelet transfusions and thus produced cost-savings compared with platelet transfusion (80% fewer prophylactic platelet transfusions, USD 4250 lower costs) or lusutrombopag (42% fewer platelet transfusions, USD 5820 lower costs) [ 91 , 92 ].…”
Section: Management Of Thrombocytopenia In Patients With Liver Dismentioning
confidence: 99%
“…For example, Mladsi et al, reported that avatrombopag reduced the need for platelet transfusions and thus produced cost-savings compared with platelet transfusion (80% fewer prophylactic platelet transfusions, USD 4250 lower costs) or lusutrombopag (42% fewer platelet transfusions, USD 5820 lower costs) [ 91 , 92 ]. Others concluded from their cost-effectiveness analysis that avatrombopag and lusutrombopag are more expensive than no TPO receptor agonist over lifetime, as savings from avoiding platelet transfusions are exceeded by the drug cost and appear to be without long-term health benefits [ 93 ]. However, such a contention disregards that platelet transfusions are inappropriate as a sustained management option in patients with chronic liver disease.…”
Section: Management Of Thrombocytopenia In Patients With Liver Dismentioning
confidence: 99%
“…However, as our model did not account for these variables, the results of our analysis are conservative and do not include these additional costs. Recently, Armstrong et al reported a systematic review and CEA of thrombopoietin receptor agonists avatrombopag ((Doptelet®; Dova Pharmaceuticals, Durham, NC, USA) and LUSU for thrombocytopenia in people with CLD needing an elective procedure 27 . Although it is not appropriate to compare our result with them due to differences in the medical environment and the model structure used in the analysis, they concluded that avatrombopag and LUSU were superior to no thrombopoietin receptor agonist in avoiding both PT and rescue therapy, but they were not cost‐effective given the lack of benefit and increase in cost under the UK setting.…”
Section: Discussionmentioning
confidence: 99%